2010
DOI: 10.2353/jmoldx.2010.090042
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of BIOMED-2 Versus Laboratory-Developed Polymerase Chain Reaction Assays for Detecting T-Cell Receptor-γ Gene Rearrangements

Abstract: Detecting clonal T-cell receptor (TCR)-␥ gene rearrangements (GRs) is an important adjunct test fordiagnosing T-cell lymphoma. We compared a recently described assay (BIOMED-2 protocol) , which targets multiple variable (V) gene segments in two polymerase chain reaction (PCR) reactions (multi-V) , with a frequently referenced assay that targets a single V gene segment in four separate PCR reactions (mono-V). A total of 144 consecutive clinical DNA samples were prospectively tested for T-cell clonality by PCR u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…Performing other BIOMED-2 reactions is needed only for the remaining 9% of cases, of which 3% are likely to show a clonal TCRB and/or TCRD gene rearrangement. Such an overall level of T-cell clonality detection rate compares well with the 94% detection rate reported in the follow-up study of the BIOMED-2 group13 and the 93–96% detection rate reported in the independent studies using BIOMED-2 assays combined with laboratory developed assays on fresh-frozen materials 30 31. Thus, approximately 5% of false negative results are expected in T-cell malignancies with adequate DNA quality.…”
Section: Discussionsupporting
confidence: 79%
“…Performing other BIOMED-2 reactions is needed only for the remaining 9% of cases, of which 3% are likely to show a clonal TCRB and/or TCRD gene rearrangement. Such an overall level of T-cell clonality detection rate compares well with the 94% detection rate reported in the follow-up study of the BIOMED-2 group13 and the 93–96% detection rate reported in the independent studies using BIOMED-2 assays combined with laboratory developed assays on fresh-frozen materials 30 31. Thus, approximately 5% of false negative results are expected in T-cell malignancies with adequate DNA quality.…”
Section: Discussionsupporting
confidence: 79%
“…Clonality analysis has been defined in the EuroClonality/BIOMED-2 consortium by the standardization of multiplex PCR assays for nearly all Ig/TCR targets (Igκ and TCRβ, incomplete IGH D-J and TCRB D-J rearrangements). These tests collectively show a high rate of detection in the most common B- and T-cell lymphomas [41,42,43,48,49]. EuroClonality/BIOMED-2 have also produced guidelines for the interpretation and for reporting results in suspected lymphoma [37].…”
Section: Pcr-based Assaysmentioning
confidence: 99%
“…Ig and TCR antigen receptor gene rearrangements are the mostly applied targets for clonality testing in NHL [42,43,48,49,50]. Ig and TCR rearrangements occur in the earliest stages of B and T cell development by the random joining of many V, (D) and J genes in a unique V(D)J exon that encodes the final antigen-binding moiety of the Ig or TCR chain [51].…”
Section: Pcr-based Assaysmentioning
confidence: 99%
“…TCR studies were performed at the time of diagnosis on formalin-fixed paraffin embedded (FFPE) tissue as previously described 14. Briefly, 20–30 sections of the FFPE tissue were cut at a thickness of 5 μm.…”
Section: Methodsmentioning
confidence: 99%